Expert Answers
justaguide eNotes educator| Certified Educator

The equation 4x + 5y = 6 has two variables x and y.

To express y in terms of x,

4x + 5y = 6

Subtract 4x from both the sides

4x + 5y - 4x = 6 - 4x

=> 5y = 6 - 4x

Divide both the sides by 5

=> (5y)/5 = (6 - 4x)/5

=> y = (6 - 4x)/5

The solution of y from the equation 4x + 5y = 6 is y = (6 - 4x)/5

oldnick | Student

`5y=6-4x`

`y=1/5(6-4x)`

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question